Metal-free graphene-carbon nitride hybrids for photodegradation of organic pollutants in water - Ai, B.; Duan, X.; Sun, Hongqi; Qiu, X.; Wang, Shaobin (Elsevier BV, 2015)
Hybrid photocatalysts of graphitic carbon nitride (g-C3N4) and reduced graphene oxide (rGO) composites were prepared in one-pot via a thermal condensation of melamine with different amounts of graphene oxide (GO). As metal-free hybrids, the prepared photocatalysts presented enhanced performances in photooxidation of both methylene blue and phenol in water solutions under various light irradiations. The level of rGO significantly affected MB photodegradation efficiencies. The introduced graphene can improve the MB adsorption and optical absorption in visible light region, therefore enables the hybrids to efficiently degrade MB under visible light with wavelengths longer than 430 nm. The metal-free photocatalysts were also able to degrade phenol effectively and the effects of catalyst loading and initial phenol concentration were investigated. This study provided an efficient and environmentally benign photocatalyst for degradation of organic pollutants in water, with complete prevention of secondary contamination from metal-leaching.